UNSUR-UNSUR SERTA HUKUM TENTANG PEMBERONTAKAN DALAM PANDANGAN ISLAM - Rahmad Alamsyah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The formulation of the problem in this study is related to the Islamic view of rebellion and punishment of rebels in Islamic criminal law. This type of research is normative legal research that specifically discusses rebellion according to Islamic law. The Islamic view of rebellion is an attempt or movement carried out by a group with the aim of overthrowing the legitimate government or subversion. The requirements for something to be considered a rebellion are rebellion against legitimate power holders and being fair in setting policies, not carried out by a few people, there is strong evidence that shows it is a movement to rebel to overthrow the legitimate government and the movement has a leadership system. The punishment for rebels in Islamic criminal law is the death penalty which aims to create a social system and government authority and is based on the consideration that without the implementation of government, society will be chaotic and people who fight against legitimate government based on Islamic law are the same as people who are against Allah SWT will and His Messenger.Key Words: Islamic Law, Criminal Law, Rebellion.